A multimodal approach to English for academic purposes in contexts of diversity. Issue 4 (30th October 2022) - Archer, Arlene
Abstract: This article focuses on the affordances of multimodal pedagogies in teaching English for academic purposes (EAP) in diverse and multilingual contexts. It draws on South Africa as an example of a multilingual, culturally diverse site in a recently decolonized country. Here theorizing and pedagogical practices around EAP often have a social justice agenda in order to redress the inequalities of the past. The importance of recognizing the multilingual and multimodal resources of students is highlighted in the teaching of academic writing. To this end, the article examines talk as an important mode in improving writing, drawing on multilingualism as a resource, working on screen versus page, the affordances of mind‐mapping and visualizing academic argument. The contention is that multimodal pedagogies can acknowledge students as agentive and creative meaning‐makers. This is particularly relevant in a context in which autonomous and decontextualized models of student support persist and students continue to be constructed as 'lacking' in resources.